Linking Positive Youth Development and Health: A Descriptive Study - Rollman, Elise. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Child Development.; Advisor: Richard Lerner.; Committee: Kerri Modry-Mandell, and Megan Mueller.; Keyword: Developmental psychology.